2016
DOI: 10.1016/j.jhsa.2015.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Clinical Deficits Following High Median Nerve Injuries

Abstract: Prognostic IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 34 publications
2
28
1
Order By: Relevance
“…1 According to traditional anatomy, a complete loss of MN motor and sensory function would be expected from such a lesion. 2 A recent critical reappraisal of clinical deficits after HMNI corroborated the findings by Boswick and Stromberg 3 in 1967 by showing that patients consistently experience absent thumb and finger index flexion, weakness of the grip and pinch, and a patchy sensory loss, mostly involving thumbindex-middle finger pulp. [2][3][4] Pronation and thumb opposition, however, are somehow relatively preserved.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…1 According to traditional anatomy, a complete loss of MN motor and sensory function would be expected from such a lesion. 2 A recent critical reappraisal of clinical deficits after HMNI corroborated the findings by Boswick and Stromberg 3 in 1967 by showing that patients consistently experience absent thumb and finger index flexion, weakness of the grip and pinch, and a patchy sensory loss, mostly involving thumbindex-middle finger pulp. [2][3][4] Pronation and thumb opposition, however, are somehow relatively preserved.…”
Section: Introductionmentioning
confidence: 58%
“…2 A recent critical reappraisal of clinical deficits after HMNI corroborated the findings by Boswick and Stromberg 3 in 1967 by showing that patients consistently experience absent thumb and finger index flexion, weakness of the grip and pinch, and a patchy sensory loss, mostly involving thumbindex-middle finger pulp. [2][3][4] Pronation and thumb opposition, however, are somehow relatively preserved. 2,4 Given its rarity, 3 the ideal reconstructive strategy is yet to be determined.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Overlap of the cutaneous territory is widespread which, after a spinal cord injury, ensures better preservation of sensory than motor function (Zancolli, ). We have demonstrated that sensation in the palm is supplied not only by the median nerve, but also by the superficial branch of the radial nerve and the LAC (Bertelli, Soldado, Lehn, & Ghizoni, ). Previous use of the LAC to reinnervate the dorsal branch of the ulnar nerve via an intercalated nerve graft indicates that the radial nerve can compensate for LAC harvesting (Oberlin, Teboul, Severin, & Beaulieu, ).…”
Section: Discussionmentioning
confidence: 99%